Association of platelet-to-lymphocyte ratio with silent brain infarcts in patients with paroxysmal atrial fibrillation. (1st September 2016) - Altintas, Ozge; Tasal, Abdurrahman; Niftaliyev, Elvin; Kucukdagli, Okkes Taha; Asil, Talip
Abstract : Objectives : In this study, we aimed to evaluate whether the inflammation as measured by increased platelet to lymphocyte ratio (PLR) predispose to silent infarcts in patients with paroxysmal atrial fibrillation (PAF). Methods : The present study investigated a total of 48 new diagnosed patients with PAF who had no signs of stroke. PLR, which was calculated as the ratio of the platelet count to the lymphocyte count, C-reactive protein and erythrocyte sedimentation rate were measured due to evaluate inflammatory state. Magnetic resonance imaging (MRI) was performed to evaluate the presence of silent brain infarcts (SBIs) in patients. We calculated CHA2 DS2 –VASc scores for stratifying the stroke risk of patients. Results : Among our study population, the mean age was 56.40 ± 8.99; 36 patients were female. The leading vascular risk factor was hypertension (45.8%). SBI was determined in 16 patients (33.3%) on MRI. It was found that a higher PLR is significantly associated with the presence of SBIs in patients with PAF ( P = .001). High PLR group showed silent lesions predominantly multiple, greater than 5 mm, bilateral and in the subcortical region; though no statistically significant differences were found in each lesion areas ( P = .214; P = .509; P = .746; P = .059, respectively). Of 16 patients who showed SBI, 1 (6.3%) patient had CHA2 DS2 –Vasc scores of 0; 7 (43.8%) patients had CHA2 DS2 –Vasc scores of 1; 6 (37.5%) patients had CHA2 DS2 -Vasc scores of 2 and 2 (12.5%) patients had CHA2 DS2 –Vasc scores of 3. We did not find any significant relationship between CHA2 DS2 –Vasc scores and presence of SBI in the study patients ( P = .850). Discussion: High PLR might be a factor to induce inflammatory process on SBIs even with low CHA2 DS2 –VASc scores.